Jin in Surah Al Jin Verses 1-7 (Comparative Study of Tafsir Kemenag and Quraish Shihab) - Feryyanto Bayu Syahniar; Ahmad Nurrrohim; Abdullah Mahmud (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Jinns are invisible beings created by God. This is one of those beings favored by the Qur'an. But the existence of jinns will always be the subject of research and attention of every circle, just like the existence of humans themselves. Besides the fact that the existence of jinns predates humans, jinns are controversial figures both among laypeople and even among scholars. But there are still many people who wonder whether jinns exist, whether humans can see them, and what are the characteristics of life? Because in the Quran, the word jinn is mentioned 34 times. This is the article that requires humans and especially Muslims to know detailed information about the existence of jinns. From there the author tries to explain simply how the Qur'an, especially in Sura Al-Jin verses 1-7 views jinns. But in this article the author will only focus on the perception of tafsir scholars, namely Tafir Ministry of Religious Affairs and Tafsir Quraish Shihab. The systematics of writing this article includes using thematic methods or maudui, namely by searching for keywords in mufradat, then analyzing the relationship between verses and comparing different verses. The author concludes tentatively that jinns were created from fire just as humans were created from the ground. Jinns are bukallaf beings like humans and in the here after they will be rewarded for all their deeds. This is why humans and jinns are called ats-tsaqalain. In today's life, genius is also understood as a virus, a type of negative human potential. They have extraordinary abilities that humans cannot perform, meaning that they do not mean that humans are inferior to jinns but according to the functions they create. In the world of jinns, there are people who are shaleh but many are evil and even unfaithful. God's purpose in creating Jinns was not just to worship and become His servants.